Characteristics of people with pressure ulcers using one year's routinely collected data in a defined diverse community. (2nd September 2019) - Jackson, Debra; Hutchinson, Marie; Neville, Stephen; Padula, William V.; Usher, Kim; Gardner, Sarah; Betteridge, Ria; Durrant, Lisa
Abstract : Objective: To determine if meaningful patient characteristics pertaining to pressure ulcers (PU) can be derived from routinely collected community health data. Methods: A retrospective cohort analysis of records was carried out. To provide a detailed dataset on PU for the community of interest, demographic, general medical and PU data were extracted from mandatory incident reports and audit of electronic and paper medical records. This study is reported in accordance with the RECORD Guidelines from the Equator Network. Adult patients were enrolled from a district nursing service in the target region (n=1085) during 2015. The target region was based on a geographical region bounded by a single postcode district (target region) consisting of 62, 000 people of whom approximately 50, 000 were adults, 3000 of whom were aged >75 years. Results: The total number of recorded PUs was n=137 in 103 individuals. Data from mandatory incident reports was obtainable for nearly all variables. Electronic and paper medical records were less reliable due to missing data. Conclusion: Detailed characteristics of community-dwelling PU patients can be derived from routinely collected data, and provides various forms and levels of information which could feed into different projects. The use of mandatory reporting fields increases the level of reporting and reduces missing data. Data enriched with information from electronic and paper records could inform the addition of variables to mandatory forms to improve characterisation of community dwellers with PUs.